Интеллектуальные уловки феноменологической социологии - Бурлачук, В. (Социология: теория, методы, маркетинг, 2008)
The paper critically analyzes the main ideas of phenomenological sociology developed by the founder of a new sociological paradigm A. Schutz. The author exposes inherent contradictions between phenomenological philosophy of E. Husserl and M. Weber’s understanding sociology. It casts doubt on a project intended to synthesize these two knowledge domains. Besides, there is demonstrated a paradoxical nature ot the idea to construct sociological theory as based on the subjective sense of Another’s activity, which should not be coincided with sense attributed by an ‘outside spectator’. The basic premise of Schutz is that sociological theory should be constructed only after analyzing activity of an individual subject named as ‘solitary Ego’. This activity is one explored by means of phenomenological method. Sociological phenomenology takes its own approach to reanimate gnoseological Robinsonada. A. Schutz makes an attempt to draw distinctions between objective and subjective sense in the activity of ‘solitary Ego’. The scholar supposes to reveal original sources of the sense in the intentional acts of consciousness. A phenomenological approach excludes analysis of the unconscious mental activity as a source for making sense. Constituting sense, as it explained by A. Schutz, should be opposed to the assertion that sense is neither created nor constituted within the frame of individual’s consciousness intentional activity. Starting from this position, the author expresses doubt regarding possibility of objective theory about subjective sense within sociology.